Bimetallic RuNi nanoparticles as catalysts for upgrading biomass: metal dilution and solvent effects on selectivity shifts. Issue 21 (14th October 2021) - Cardona-Farreny, Miquel; Lecante, Pierre; Esvan, Jerome; Dinoi, Chiara; del Rosal, Iker; Poteau, Romuald; Philippot, Karine; Axet, M. Rosa
Abstract : Core–shell RuNi catalysts are prepared from organometallic complexes and PVP as stabilizers under one-pot conditions. The synergistic effect between Ru and Ni activity in furfural hydrogenation depends on the nanoparticle composition. Abstract : RuNi nanoparticles (NP) were prepared by decomposition of [Ru(η 4 -C8 H12 )(η 6 -C8 H10 )] and [Ni(η 4 -C8 H12 )2 ] by H2 in the presence of polyvinylpyrrolidone (PVP) at 85 °C using several Ru/Ni ratios. The nanoparticles display a segregated structure in which Ni is on the surface, as ascertained by wide angle X-ray scattering (WAXS). The catalytic activity in the selective hydrogenation of furfural of these RuNi NP was correlated with the Ru content. High selectivity towards the partially hydrogenated product 2-(hydroxymethyl)furan (HF) was found when carrying out the reaction in tetrahydrofuran (THF). A different scenario was found when using a protic polar solvent, 1-propanol. Catalysts displaying Ru on the surface were able to hydrogenate the heteroaromatic ring, while those with Ni on the surface were highly selective towards the partially hydrogenated product. In addition, Ru surfaces were prone to catalyse the acetalization reaction in the presence of the alcoholic solvent, while the addition of Ni supressed this reactivity. Density functional theory (DFT) calculations performed on hydrogenated Ru nanoparticles (Ru55 H70 ) show differences in the adsorption energies of several reagents, products, reaction intermediates, and solvents onto the Ru NP surface, which are in line with the experimental catalytic results.